Breakthrough Filamentous Fungal Infections in Pediatric Hematopoetic Stem Cell Transplant and Oncology Patients Receiving Caspofungin - Shaun K Morris; Upton D Allen; Sumit Gupta; Susan E Richardson (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Caspofungin is an echinocandin class antifungal medication that is commonly used empirically in immunocompromised patients at high risk for invasive fungal disease.